Supervisor bottom line mentality and its impact on employee outcomes: The mediating role of employee appraisals - Zainab Naseer; Sayyed Muhammad Mehdi Raza Naqvi (PLoS ONE, 2026)
The concept of Bottom-line mentality (BLM) has been increasingly emphasized in contemporary workplaces, often at the expense of other critical organizational priorities. However, its implications for employees have remained underexplored. This study, which investigates how supervisors’ BLM influences employees’ behaviors and perceptions in the workplace, underscores the need for a balanced approach to leadership. Using SmartPLS 4, survey data from 382 employees in Pakistan’s fast-moving consumer goods sector were analyzed. The results reveal that supervisor BLM is positively associated with employee incivility and negatively associated with employees’ goal progress. Furthermore, employees’ hindrance appraisals mediate the relationship between supervisor BLM and incivility, whereas challenge appraisals mediate the relationship between supervisor BLM and goal progress. This research extends the literature by clarifying how supervisors’ bottom-line focus shapes employee actions and work outcomes, and it highlights the importance of a balanced leadership approach. The findings suggest that although leaders may adopt a bottom-line mentality to enhance performance, its effectiveness depends on how employees interpret and respond. The study offers practical guidance for organizations seeking to strengthen feedback systems and reduce the negative effects of supervisory misconduct.